The Polish regional labour market welfare indicator and its links to other well-being measures - Marek Ręklewski; Maciej Ryczkowski (Comparative Economic Research. Central and Eastern Europe, 2016)
We propose and construct an indicator of labour market well-being in Poland for the year 2013. The indicator is positively related to the degree of civilizational welfare, social welfare, material welfare and psychological well-being in Poland. We conclude that ameliorating the labour market situation improves the quality of the public's life. The link between our labour market indicator and the total fertility rate turned out to be statistically insignificant.
Keywords: 330; labour market; Weber median; delimitation; well-being indicators; welfare economics